Implementation and challenges of international atomic energy agency/american association of physicists in medicine trs 483 formalism for field output factors and involved uncertainties determination in small fields for tomotherapy - Rajesh Kinhikar; Suryakant Kaushik; Chandrashekhar Tambe; Sudarshan Kadam; Shrikant Kale; Rituraj Upreti (Journal of Medical Physics, 2021)
Purpose International Atomic Energy Agency published TRS-483 to address the issues of small field dosimetry. Our study calculates the output factor in the small fields of TomoTherapy using different detectors and dosimetric conditions. Furthermore, it estimates the various components of uncertainty and presents challenges faced during implementation. Materials and Methods Beam quality TPR20,10(10) at the hypothetical field size of 10 cm × 10 cm was calculated from TPR20,10(S). Two ionization chambers based on the minimum field width required to satisfy the lateral charge particle equilibrium and one unshielded electron field diode (EFD) were selected. Output factor measurements were performed in various dosimetric conditions. Results Beam quality TPR20,10(10) has a mean value of 0.627 ± 0.001. The maximum variation of output factor between CC01 chamber and EFD diode at the smallest field size was 11.80%. In source to surface setup, the difference between water and virtual water was up to 9.68% and 8.13%, respectively, for the CC01 chamber and EFD diode. The total uncertainty in the ionization chamber was 2.43 times higher compared to the unshielded EFD diode at the smallest field size. Conclusions Beam quality measurements, chamber selection procedure, and output factors were successfully carried out. A difference of up to 10% in output factor can occur if density scaling for electron density in virtual water is not considered. The uncertainty in output correction factors dominates, while positional and meter reading uncertainty makes a minor contribution to total uncertainty. An unshielded EFD diode is a preferred detector in small fields because of lower uncertainty in measurements compared to ionization chambers.